Impact of displacement on the psychological well-being of refugee children - Ajduković, Marina (Array, 1998)
The war-related stress had a negative impact on the psychological well-being of all children in Croatia, but displaced and refugee children were especially affected. Although refugee children showed impressive resilience, particular attention should be devoted to children who had traumatic experiences immediately prior to displacement. These children either lived without their parents or with parents who had poor coping abilities while displaced; lived in families that had accumulated several stressful experiences; or were housed in large collective refugee centers. The children that had poorer coping capacities and lacked a supportive family environment displayed high levels of stress-related symptomatology throughout the entire refugee period, being at special risk for the development of further psychological difficulties. The findings reported in this study are the result of a five-year follow-up of the same group of refugee children. Data about children's coping abilities with displacement were obtained primarily from mothers and the children themselves.